KRITIK SASTRA FEMINIS DAN INTERTEKSTUALITAS DALAM KISAH LAYLÂ MAJNÛN DAN ROMEO JULIET - Hanik Mahliatussikah (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstract: This material is chosen due to some factors; popular, interesting, and problematic. The intended goal is to reveal the roles, functions, and positions of Arab and Western women in the kisahs Laylâ Majnûn and Romeo and Juliet; to portrait the mental and spiritual characters, and the behaviors, expressed by Arab and Western women in both works; and to reveal the intertextual relation of both works. It is  descriptive qualitative research and done through the process of the coding, the classification, the analysis, and the interpretation of the data. The role dominations, functions, and positions, of Arab and western women are in the scope of family environment. In both stories, women have good mental and spiritual characteristics. The woman in Romeo and Juliet is imaged to be more aggressive than the woman in Laylâ Majnûn. There is an intertextual relations in the ideas of both works. Considering the superiority of the story of Laylâ Majnûn which has exceeded the eastern society and its prior existence compared to Romeo and Juliet, the story of Laylâ Majnûn can become the hypogram. The transformations done by Shakespeare in the story of Romeo and Juliet are not only in the title, theme, and characters, but also the plot of the story. The transformation of the monumental story of Romeo and Juliet shows that Shakepeare has the creativity in arranging stories and sentences that the story of Romeo and Juliet appears to be a new masterpeace which is not a borrowing from the story of Laylâ Majnûn. keywords: the image of woman, laylâ majnûn, romeo juliet, feminist literary criticsm, intertekstuality